Assessment and optimization plan for enhancing public medical laboratory services in the Kyrgyz Republic. - Taalaigul Sabyrbekova; Elmira Turkmenova; Ping Ling Yeoh; Olga Slobodskaya; Cebele Wong; Brian Chin (PLOS Global Public Health, 2025)
Middle-income and especially low-income countries continuously seek ways to efficiently utilize their public funds to provide access to quality healthcare for their population. The government of the Kyrgyz Republic is embarking on a Strengthening Regional Health Security Project for the optimization and centralization of medical laboratories, which will be implemented as a pilot in two major cities and two regions of the country to improve essential laboratory testing for disease surveillance and diagnostics. Representative state-funded laboratories (6 bacteriological public health laboratories and 11 clinical diagnostic laboratories) were assessed using the World Health Organization's Laboratory Assessment Tool that covered the provision of services, condition of facilities, equipment, financing, reagent procurement, workflow, regulatory documents, and quality control and assurance. The five greatest weaknesses across the laboratories were identified as: (i) weak organization and management of laboratory, (ii) insufficient documentation management, (iii) inadequate facilities for biosafety, (iv) lack of biorisk management, and (v) unmet public health functions. The results of the assessment informed the design and development of a laboratory optimization master plan, including procurement of equipment and reagents, professional development of laboratory staff, and establishing laboratory networks starting with selected laboratories in two regions of the country. The restructuring, upgrading, and continuous quality improvement of laboratory networks will be achieved through strengthening governance capacity for the national laboratory system including regulation, standards, planning, financing, management, monitoring, and studies for innovative solutions. The approach to assessing the current situation and creating an improvement plan for optimizing laboratory services may be useful to countries facing similar challenges.